The regularities of the formation of metal-glass materials and coatings with enhanced X-ray properties - Казимиренко, Юлия Алексеевна (Technology audit and production reserves, 2013)
This article discusses the use of new metal-glass materials and electric coatings for protection against X-ray radiation. The purpose of research is to establish regularities of formation of metal-glass materials and coatings, offering enhanced X-protective properties. Experimentally investigated the structure and X-ray protective properties: the mass attenuation coefficient of X-ray radiation and the specific lead equivalent to glass-aluminum composite materials and electric-arc coating of Sv-08G2S and Sv-AMg5 filled with hollow glass microspheres , powders of sodium silicate and the leaded glass . Established the attenuation effect of X-ray radiation by hollow glass microspheres, solid particles of liquid silicate the leaded glass, substructural elements formed as a result of heat treatment. Established regularities allow to manage the processes of formation of x-ray protective properties. The research results can be applied to the design of protection against the effects of X-ray emission for hardware, energy facilities, transportation, and medicine.